(untitled) (The Review of Diabetic Studies, 2025)
Background: Remote cardiac monitoring systems have become integral in managing arrhythmias and heart failure by enabling continuous patient observation and timely interventions. These systems include wearable sensors, implantable devices, and mobile applications that transmit electrocardiogram or photoplethysmography data to clinicians in real time. Objective: This systematic review aimed to evaluate the effectiveness of remote monitoring systems in improving clinical outcomes for patients with cardiac arrhythmias, including atrial fibrillation and heart failure–related rhythm disturbances. Methods: A comprehensive search of PubMed, Scopus, Web of Science, Embase, and Google Scholar was conducted for studies published between January 2005 and December 2025. Eligible studies included RCTs, observational studies, and diagnostic validation trials assessing telemonitoring, mobile health, implantable devices, or wearable sensors in adult patients. Key outcomes included mortality, hospital readmissions, treatment adherence, diagnostic accuracy, and healthcare resource utilization. Data were synthesized narratively due to heterogeneity in study designs and interventions. Results: Eleven studies met inclusion criteria. Telemonitoring interventions involving automated or daily device-based data transmission improved clinical efficiency, adherence, and response times to arrhythmic events. Implantable device remote monitoring demonstrated significant reductions in hospitalizations and optimized therapy, while telephone-based or manual systems yielded limited improvements. Mobile and wearable applications exhibited high diagnostic accuracy for atrial fibrillation detection. Conclusion: Remote monitoring systems, particularly those utilizing automated or implantable technologies, enhance clinical management of cardiac arrhythmias, improve adherence, and optimize healthcare utilization.